2010
DOI: 10.1111/j.1365-2982.2010.01603.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory role of glycine in reducing rodent postoperative inflammatory ileus

Abstract: Background-Inflammatory events within the intestinal muscularis, including macrophage activation and leukocyte recruitment, have been demonstrated to participate in causing postoperative ileus. Recently, glycine has gained attention due to its beneficial immunomodulatory effects in transplantation, shock and sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 68 publications
1
40
0
1
Order By: Relevance
“…Small peptides and amino acids derived from CH are detectable in blood. 10,19 The present study demonstrated that orally administered CH increases plasma glycine levels in mice in a concentrationdependent manner. Anti-inflammatory effectiveness was indicated by counteraction of the zymosan-induced ear swelling at 3 h after zymosan injection (5 h after CH intake).…”
Section: Discussionmentioning
confidence: 84%
“…Small peptides and amino acids derived from CH are detectable in blood. 10,19 The present study demonstrated that orally administered CH increases plasma glycine levels in mice in a concentrationdependent manner. Anti-inflammatory effectiveness was indicated by counteraction of the zymosan-induced ear swelling at 3 h after zymosan injection (5 h after CH intake).…”
Section: Discussionmentioning
confidence: 84%
“…The regulation of the COX isoforms by glycine was reported previously; oral administration reduced the expression of COX-1 and COX-2 in the kidneys of rats with metabolic syndrome (Pérez-Torres et al 2011). Additionally, glycine pretreatment attenuated the elevated production of prostanoids derived from COX-2 in postoperative ileum experiments (Stoffels et al 2011).…”
Section: Figmentioning
confidence: 82%
“…Secondly, Avertin use was associated with ileus or peritonitis in a subset of mice, a side effect previously reported by others [33,74]. While these mice were excluded from the analyses (fig.…”
Section: Discussionmentioning
confidence: 99%
“…1). Study exclusions were related to mortality at the time of impact, euthanasia due to skull fracture or malocclusion, or morbidity associated with the development of intestinal ileus in a subset of mice anaesthetized by Avertin (2,2,2-tribromoethanol), a side effect previously reported by others [32,33]. Standard bedding, rodent chow, and water were available ad libitum, and housing was maintained on a 12-hour light/dark cycle at approximately 20°C.…”
Section: Methodsmentioning
confidence: 99%